Analisis Putusan Pengadilan Agama Kota Kediri Nomor 0018/Pdt.P/2020/PA.Kdr tentang Dispensasi Kawin - Nuril Fahmi; Nur Hikmah; Moh. Usvi; Devi Nur; Eka Chandra; Sanuri Sanuri (Laboratorium Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2021)
Abstract: This study aims to analyze the Kediri Religious Court Number 0018/Pdt.P/2020/PA decision.Kdr. About Marriage Dispensation. Marriage dispensation has the meaning of an exception from the general rule for exceptional circumstances concerning the age of marriage, namely relief from restrictions. In the case of a marriage dispensation application filed at the Kediri Religious Court, the judge granted the Petitioner's request with a marriage dispensation to his 18-year-old daughter. The verdict is based on evidence and witnesses in court. Among the witness statements are that although the daughter is still 18 years old, she is already good at taking care of the housework, the husband-to-be who works as an entrepreneur earns Rp. 2,500,000 every month, the prospective bride and groom have been in love for two years, so the marriage is done to prevent forbidden things between them. In the perspective of Islamic law, the request is by the fiqh rule